Exploring the Influence of Sociocultural and Parenting Styles on Enhancing Children's English Learning: A Narrative Case Study from Indonesia - Nada, Nabilah; Nukmatus Syahria; Nico Irawan (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2025)
This study explores sociocultural factors based on Bourdieu’s theory (1987) and parenting styles based on Baumrind's theory (1991) to support children's EFL learning, emphasizing the perspectives and experiences of parents and families. This narrative case study encompasses six parents with children aged 5 to 11 years and families from diverse regions in Indonesia. Data were collected through semi-structured interviews and analysis of children's English language practice video documents. They were analyzed through deductive thematic analysis with NVivo software to explore prominent themes. The results reveal that sociocultural factors, predominantly the theme of social capital, supported by the role of habitus and cultural capital, alongside the authoritative parenting style, as reflected through parents' perspectives and experiences, with family support in have affected children's EFL learning. Moreover, sociocultural factors and parenting styles can also proficiently convey EFL learning values and foster a positive environment for English learning. It can be implied that the research has beneficial for the parents’ roles in creating a positive learning environment through balanced engagement of sociocultural factors and the utilization of appropriate parenting styles. Nonetheless, if the sociocultural factors are less than optimal, this is not a hitch because the appropriate parenting style can support them.